1997
DOI: 10.1006/jmbi.1997.1405
|View full text |Cite
|
Sign up to set email alerts
|

Inter-domain cross-linking and molecular modelling of the hairpin ribozyme

Abstract: The hairpin ribozyme is a small catalytic RNA composed of two helical domains containing a small and a large internal loop and, thus, constitutes a valuable paradigm for the study of RNA structure and catalysis. We have carried out molecular modelling of the hairpin ribozyme to learn how the two domains (A and B) might fold and approach each other. To help distinguish alternative inter-domain orientations, we have chemically synthesized hairpin ribozymes containing 2 H -2 H disulphide linkages of known spacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 62 publications
(95 reference statements)
4
90
3
Order By: Relevance
“…The overall topology structure of the extended kissing complex is similar to some other RNA four-way junctions (Krol et al+, 1990;Walter et al+, 1998a;Nowakowski et al+, 1999) and DNA Holliday junctions (Duckett et al+, 1992)+ In both DNA and RNA four-way junctions, divalent ions are required for the formation and stabilization of antiparallel X-shaped structures (Duckett et al+, 1992;Walter et al+, 1998b)+ The particularity of the proposed CopA-CopT structure is the crossing over of the strands at the junction under the constraints imposed by the two loops connecting intermolecular helices B and B9+ This forces a side-by-side alignment of the two helical domains that brings the 59 tail of CopA in close proximity to the complementary region of CopT (Fig+ 7)+ The formation of intermolecular helix C, which clamps the two long helical domains, greatly enhances the stability of the complex (Persson et al+, 1990a;Malmgren et al+, 1997)+ Crystallographic analysis of a group I ribozyme domain revealed a similar organization (Cate et al+, 1996): a sharp bend induced by an internal loop allows a side-by-side alignment of two helical domains that is additionally stabilized by metal-and ribosemediated backbone contacts and two long-range tertiary interactions+ A side-by-side configuration was also proposed for the hairpin ribozyme, here stabilized by interactions between two internal loops (Earnshaw et al+, 1997)+ The formation of a stable RNA-RNA complex is not unique to CopA-CopT, and is also a key feature in the replication control of plasmids belonging to the IncB and IncIa groups (Siemering et al+, 1994; plasmids+ In these systems, the antisense RNAs inhibit the formation of a pseudoknot structure that activates rep translation (Wilson et al+, 1993;)+ All these antisense and target RNAs are characterized by stable hairpins with identical loop sequences and bulged residues in the upper stem regions+ Enzymatic probing performed on (antisense) RNAI in pMU720 plasmid bound to its target indicated that a full duplex was not rapidly formed in vitro+ Instead, binding resulted in an extended kissing complex stabilized by 59 tail interactions (Siemering et al+, 1994)+ One may therefore speculate that, in all these systems, the final product of the binding reaction in vitro is characterized by an overall topology very similar to that reported here, except that the lengths of helices B and B9, if formed in the IncB/IncIa cases, could be different+…”
Section: Conversion Of a Loop-loop Interaction To A Four-helix Junctionmentioning
confidence: 94%
“…The overall topology structure of the extended kissing complex is similar to some other RNA four-way junctions (Krol et al+, 1990;Walter et al+, 1998a;Nowakowski et al+, 1999) and DNA Holliday junctions (Duckett et al+, 1992)+ In both DNA and RNA four-way junctions, divalent ions are required for the formation and stabilization of antiparallel X-shaped structures (Duckett et al+, 1992;Walter et al+, 1998b)+ The particularity of the proposed CopA-CopT structure is the crossing over of the strands at the junction under the constraints imposed by the two loops connecting intermolecular helices B and B9+ This forces a side-by-side alignment of the two helical domains that brings the 59 tail of CopA in close proximity to the complementary region of CopT (Fig+ 7)+ The formation of intermolecular helix C, which clamps the two long helical domains, greatly enhances the stability of the complex (Persson et al+, 1990a;Malmgren et al+, 1997)+ Crystallographic analysis of a group I ribozyme domain revealed a similar organization (Cate et al+, 1996): a sharp bend induced by an internal loop allows a side-by-side alignment of two helical domains that is additionally stabilized by metal-and ribosemediated backbone contacts and two long-range tertiary interactions+ A side-by-side configuration was also proposed for the hairpin ribozyme, here stabilized by interactions between two internal loops (Earnshaw et al+, 1997)+ The formation of a stable RNA-RNA complex is not unique to CopA-CopT, and is also a key feature in the replication control of plasmids belonging to the IncB and IncIa groups (Siemering et al+, 1994; plasmids+ In these systems, the antisense RNAs inhibit the formation of a pseudoknot structure that activates rep translation (Wilson et al+, 1993;)+ All these antisense and target RNAs are characterized by stable hairpins with identical loop sequences and bulged residues in the upper stem regions+ Enzymatic probing performed on (antisense) RNAI in pMU720 plasmid bound to its target indicated that a full duplex was not rapidly formed in vitro+ Instead, binding resulted in an extended kissing complex stabilized by 59 tail interactions (Siemering et al+, 1994)+ One may therefore speculate that, in all these systems, the final product of the binding reaction in vitro is characterized by an overall topology very similar to that reported here, except that the lengths of helices B and B9, if formed in the IncB/IncIa cases, could be different+…”
Section: Conversion Of a Loop-loop Interaction To A Four-helix Junctionmentioning
confidence: 94%
“…Recently, a computer-generated tertiary model was made that was based on preexisting structural data and on the spatial distance of tolerated, interdomain, aryl-disul¢de crosslinks [85]. Additional information was also obtained by Walker et al [86] using FRET data.…”
Section: Hairpin Ribozymementioning
confidence: 99%
“…The G + 1 · C25 base pair was identified by hydroxyl-radical protection, covalent crosslinking, molecular modeling, and compensatory base substitutions (Pinard et al 1999b). A conventional ribose zipper links the N3 atoms of A10 and A24 with the 2Ј-hydroxyl groups of nucleotides 10, 11, 24, and 25 (Earnshaw et al 1997). Each of these interactions has been confirmed by the crystallographic structure (Rupert and Ferré-D'Amaré 2001), and is observed in detailed models of the ribozyme-substrate complex that we have recently developed (Pinard et al 1999b(Pinard et al , 2001a.…”
Section: Introductionmentioning
confidence: 99%